Effects of Eurycoma longifolia Jack supplementation on eccentric leg press exercise-induced muscle damage in rugby players - Zakaria, Ahmad; Washif, Jad; Lim, Boon; Nosaka, Kazunori (Biology of Sport, 2023)
Eurycoma longifolia Jack (ELJ) is a herbal plant that has androgenic and antioxidant effects. We investigated the short-term effect of ELJ supplementation on muscle damage induced by eccentric exercise. Eighteen young (19–25 years), well-trained rugby 7s players were assigned to an ELJ or a placebo (PLA) group (n = 9/group). Each participant took four 100-mg capsules a day for seven days prior to performing a leg press eccentric exercise to failure in a double-blind fashion. Peak force, peak power and jump height in countermovement jump (CMJ), drop jump reactive strength index (RSI), muscle soreness assessed by a 100-mm visual analogue scale, plasma creatine kinase (CK) activity, and salivary hormones were measured at 24 h before and 0.5, 24, 48, 72, and 96 h after the exercise. Changes in the variables over time were compared between the groups by two-factor mixed-design ANOVA. The number of eccentric contractions performed was similar (P = 0.984) between the ELJ (21±5) and PLA groups (21±5). Salivary testosterone and cortisol concentrations did not change (P > 0.05) after the supplementation for both groups. CMJ peak power (-9.4 ±5.6%) and height (-10.6±4.9%), and RSI (-15.2±16.2%) decreased at 24 h after exercise (P < 0.05), and muscle soreness (peak: 89 ±10 mm) and plasma CK activity (peak: 739±420 IU/L) increased after exercise (P < 0.05) without significant differences between groups. These results showed that 7-day ELJ supplementation prior to the leg press eccentric exercise had no significant effects on hormones, performance and muscle damage markers for the athletes